2018
DOI: 10.1109/tnsre.2018.2810859
|View full text |Cite
|
Sign up to set email alerts
|

How are Muscle Synergies Affected by Electromyography Pre-Processing?

Abstract: Muscle synergies have been used for decades to explain a variety of motor behaviors, both in humans and animals and, more recently, to steer rehabilitation strategies. However, many sources of variability such as factorization algorithms, criteria for dimensionality reduction and data pre-processing constitute a major obstacle to the successful comparison of the results obtained by different research groups. Starting from the canonical EMG processing we determined how variations in filter cut-off frequencies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 69 publications
(130 reference statements)
4
56
0
Order By: Relevance
“…However, there are also other elements of the processing chain giving raise to the muscle synergies extraction that must be considered. In general, prior literature has drawn considerable attention to the influence of EMG pre-processing on muscle synergy extraction [34]- [36]. In particular, the importance of standardization in envelope estimation [37] and amplitude normalization [38], [39] were thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also other elements of the processing chain giving raise to the muscle synergies extraction that must be considered. In general, prior literature has drawn considerable attention to the influence of EMG pre-processing on muscle synergy extraction [34]- [36]. In particular, the importance of standardization in envelope estimation [37] and amplitude normalization [38], [39] were thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Alternate methods of scaling synergies experimentally, such as by a maximum voluntary contraction or the use of force-to-EMG measurements (Borzelli et al, 2013), require the collection and integration of additional data, significantly complicating the implementation. Although the choice of amplitude scaling prior to calculating synergies can impact the relative weights of muscles within a given synergy (Shuman et al, 2017), a recent investigation by Kieliba et al (2018) found nearly identical synergy structures between EMG data normalized by maximum voluntary contractions or peak activations in healthy adults. The consistency of these synergy structures suggests that the relative weights of muscles within a synergy scaled by experimental data may only have a small impact on our results.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the signals were rectified and low-pass-filtered with a zero-lag, fourth-order, Butterworth filter (5 Hz) [31]. The maximal EMG amplitude of each muscle per repetition was extracted and averaged within a set to create a normalizing factor [32]. EMG amplitude of each muscle per lifting set was divided by the normalizing factor.…”
Section: Data Processingmentioning
confidence: 99%